Krill Oil Alleviated Methamphetamine-Induced Memory Impairment via the MAPK Signaling Pathway and Dopaminergic Synapse Pathway - Ru, Qin; Tian, Xiang; Xiong, Qi; Xu, Congyue; Chen, Lin; Wu, Yuxiang (Frontiers in Pharmacology, 2021)
Methamphetamine (METH) abuse exerts severe harmful effects in multiple organs, especially the brain, and can induce cognitive dysfunction and memory deficits in humans. Krill oil is rich in polyunsaturated fatty acids, while its effect on METH-induced cognitive impairment and mental disorders, and the underlying mechanism remain unknown. The aim of the present study was to investigate the protective effect of krill oil on METH-induced memory deficits and to explore the molecular mechanisms by using an integrated strategy of bioinformatics analysis and experimental verification. METH-exposed mice were treated with or without krill oil. Learning and memory functions were evaluated by the Morris water maze. The drug–component–target network was constructed in combination with network pharmacology. The predicted hub genes and pathways were validated by the Western blot technique. With krill oil treatment, memory impairment induced by METH was significantly improved. 210 predicted targets constituted the drug–compound–target network by network pharmacology analysis. 20 hub genes such as DRD2, MAPK3, CREB, BDNF, and caspase-3 were filtered out as the underlying mechanisms of krill oil on improving memory deficits induced by METH. The KEGG pathway and GO enrichment analyses showed that the MAPK signaling pathway, cAMP signaling pathway, and dopaminergic synapse pathway were involved in the neuroprotective effects of krill oil. In the hippocampus, DRD2, cleaved caspase-3, and γ-H2AX expression levels were significantly increased in the METH group but decreased in the krill oil–treated group. Meanwhile, krill oil enhanced the expressions of p-PKA, p-ERK1/2, and p-CREB. Our findings suggested that krill oil improved METH-induced memory deficits, and this effect may occur via the MAPK signaling pathway and dopaminergic synapse pathways. The combination of network pharmacology approaches with experimental validation may offer a useful tool to characterize the molecular mechanism of multicomponent complexes.